2011
DOI: 10.1016/j.jvs.2011.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin receptor blockers and antiplatelet agents are associated with improved primary patency after arteriovenous hemodialysis access placement

Abstract: Our data suggest that therapy with an ARB plus antiplatelet agent is associated with prolonged autogenous access primary patency, and therapy with an ARB with or without antiplatelet agents is associated with prolonged prosthetic access primary patency. Randomized studies are needed to confirm the causal role of ARBs and to determine the optimal therapeutic regimen (dose, timing, and duration) to promote access patency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…Jackson et al reported that ARB prolongs primary patency in both AVF and AVG groups [12], whereas the DOPPS study [13] showed that there’s no relationship between ARB and vascular access patency, neither in AVF or AVG. However, there is a relatively low rate of ARB use in the DOPPS population (3.8% in AVG group, and 4.1% in AVF group).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Jackson et al reported that ARB prolongs primary patency in both AVF and AVG groups [12], whereas the DOPPS study [13] showed that there’s no relationship between ARB and vascular access patency, neither in AVF or AVG. However, there is a relatively low rate of ARB use in the DOPPS population (3.8% in AVG group, and 4.1% in AVF group).…”
Section: Discussionmentioning
confidence: 99%
“…Many strategies have been surveyed in order to prolong vascular access patency, including meticulous pre-operative planning [7], newer design of vascular access [8], stent implantation [9,10], far infrared therapy [11], and pharmacotherapy [1216]. Among pharmacotherapy, some cardioprotective antihypertensive agents have drawn attention recently, including angiotensin converting enzyme inhibitor (ACE-I), angiotensin receptor blocker (ARB) and calcium channel blocker (CCB).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RAAS plays an important role in vascular proliferation via induction of extracellular matrix and smooth muscle cell proliferation . Based on predominantly preclinical studies, RAAS blockade by ACEI or ARB has been shown to reduce intimal hyperplasia formation, promote vasodilation and prevent platelet activation and adhesion (Figure ).…”
Section: Biological Rationale For Using Acei/arb To Improve Vascular mentioning
confidence: 99%
“…Agents such as fish oil and angiotensin-converting enzyme inhibitors have shown some effect in increasing the patency in AV grafts and fistulas [44] . Jackson et al [45] suggest that therapy with an ARB plus antiplatelet agent is associated with prolonged autogenous access primary patency and therapy with an ARB with or without antiplatelet agents is linked with prolonged prosthetic access primary patency. Although arterial image quality and vessel-to-background ratios were lower, NCE-MRA is considered as a feasible alternative to CE-MRA in patients with ESRD who need imaging of the upper extremity and central vasculature prior to dialysis access creation [46] .…”
Section: Permanent Vamentioning
confidence: 99%